A novel dendrimer-based complex co-modified with cyclic RGD hexapeptide and penetratin for noninvasive targeting and penetration of the ocular posterior segment. (1st January 2019) - Yang, Xiucheng; Wang, Lihua; Li, Lin; Han, Meishan; Tang, Shengnan; Wang, Tengteng; Han, Junping; He, Xiaoyan; He, Xiuting; Wang, Aiping; Sun, Kaoxiang
Abstract: Noninvasive drug delivery is a promising treatment strategy for ocular posterior segment diseases. Many physiological and anatomical barriers of the eye considerably restrict effective diffusion of therapeutics to the target site. To overcome this problem, a novel cyclic arginine-glycine-aspartate (RGD) hexapeptide and penetratin (PEN) co-modified PEGylation polyamidoamine (PAMAM) was designed as a nanocarriers (NCs), and its penetrating and targeting abilities were evaluated. In this study, we show that PAMAM-PEG (reaction molar ratio 1:32) has a relatively high grafting efficiency and low cytotoxicity. The particle size was within the range of 15–20 nm after modification with RGD and PEN. Cellular uptake of RGD-modified NCs involved significant affinity toward integrin αvβ3, which validated the targeting of neovasculature. An in vitro permeation study indicated that modification with PEN significantly improved penetration of the NCs (1.5 times higher). In vivo ocular distribution studies showed that, the NCs (modified with PEN or co-modified with RGD and PEN) were highly distributed in the cornea and retina ( p  < .001), and modification extended retinal retention time for more than 12 h. Therefore, these NCs appear to be a promising noninvasive ocular drug delivery system for ocular posterior segment diseases.